2021
DOI: 10.5334/aogh.3250
|View full text |Cite
|
Sign up to set email alerts
|

Health Management Workforce Capacity-Building in Liberia, Post-Ebola

Abstract: Following the Ebola crisis in Liberia in 2014-15, the Liberian Ministry of Health developed a strategy to build a fit-for-purpose health workforce, focusing on both health care providers and health managers. To help fulfill national capacity-building goals for health management, a team of faculty, staff, and practitioners from the Yale School of Medicine,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This study also found that the historical HBV infection rate among pregnant women is only about 30.0%, with most of them unaware of their infection during pregnancy or a past period, leading to missed interventions. To address these issues, this study introduced the Health Management Team (HMT) method on top of the PMTCT model, with an organizational structure similar to Liberia’s health management plan but more targeted [ 18 ]. Comprising healthcare professionals from various institutions and fields, the HMT, through clear division of labor and efficient deployment, streamlined the workflow, further standardized the processes, and enhanced management oversight, ensuring the effective application of the PMTCT model.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that the historical HBV infection rate among pregnant women is only about 30.0%, with most of them unaware of their infection during pregnancy or a past period, leading to missed interventions. To address these issues, this study introduced the Health Management Team (HMT) method on top of the PMTCT model, with an organizational structure similar to Liberia’s health management plan but more targeted [ 18 ]. Comprising healthcare professionals from various institutions and fields, the HMT, through clear division of labor and efficient deployment, streamlined the workflow, further standardized the processes, and enhanced management oversight, ensuring the effective application of the PMTCT model.…”
Section: Discussionmentioning
confidence: 99%